ACADEMIC INTEGRITY AND FIGHTING PLAGIARISM WITH TECHNOLOGY - Tkachenko, Sergi P. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Of particular importance for the scientific and educational community assumes the concept of academic integrity. In the context of weak corporate culture of the academic community and the mass tolerance violations and corrupt practices within the system is a further development of the Academic integrity plays a key role. Fighting plagiarism is not just a struggle against the consequences of this phenomenon, but it is a complex battle with the consequences and with the causes.